The role of synergistic interplay among proactive personality, leader creativity expectations, and role clarity in stimulating employee creativity - Wang, Xiaohong; Wang, Meng; Xu, Feng (Frontiers in Psychology, 2022)
This study investigates the interplay among proactive personality, leader creativity expectations, and role clarity in stimulating employee creativity based on the theoretical frameworks of role theory. Questionnaires were distributed to obtain 290 leader-employee dyads from China to examine hypotheses via conditional process analysis. The results show that proactive personality has a positive effect on employee creativity, leader creativity expectations did not play a significant moderating role on the relationship between proactive personality and employee creativity. The interaction between leader creativity expectations and role clarity has a significant moderating effect on the relationship between proactive personality and employee creativity. These findings are discussed in terms of their theoretical and practical significance.